2022
DOI: 10.1093/eurjpc/zwac056.170
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and knowledge of pneumococcal vaccination in cardiology outpatient clinics and impact of physicians' recommendation on vaccination rates

Abstract: Funding Acknowledgements Type of funding sources: None. Background Although there is not enough data on pneumococcal vaccination status in patients with cardiovascular disease and or risk factors in our country, it is known that vaccination rates are quite low in the current data. Purpose We aimed to evaluate the awareness of pneumococcal vaccination (PCV13, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Consistent with our finding of lacking physician’s vaccination recommendation being a major determinant of negative vaccination status, Lindsley et al [ 29 ] concluded that vaccination recommendation resulted in increased vaccination rates in patients treated with immunosuppressants due to a dermatological condition. This effect was also identified in other patient populations, for example in diabetic and cardiology patients, indicating that awareness about the beneficial aspects of vaccination brought forward by physicians proves to have a positive influence on vaccination status [ 30 , 31 ]. Informational campaigns by healthcare professionals and providers could address the patient’s fear of contracting pneumonia and establish confidence in the vaccination [ 32 ].…”
Section: Discussionmentioning
confidence: 87%
“…Consistent with our finding of lacking physician’s vaccination recommendation being a major determinant of negative vaccination status, Lindsley et al [ 29 ] concluded that vaccination recommendation resulted in increased vaccination rates in patients treated with immunosuppressants due to a dermatological condition. This effect was also identified in other patient populations, for example in diabetic and cardiology patients, indicating that awareness about the beneficial aspects of vaccination brought forward by physicians proves to have a positive influence on vaccination status [ 30 , 31 ]. Informational campaigns by healthcare professionals and providers could address the patient’s fear of contracting pneumonia and establish confidence in the vaccination [ 32 ].…”
Section: Discussionmentioning
confidence: 87%